Data Science to Analyze the Flipped Classroom in the Educational Process of Geography - Salas-Rueda, Ricardo-Adán; Ledesma-Alexander, Leonardo; Domínguez-Herrera , Eduardo (Revista Ecos de la Academia, 2024)
This mixed study was aimed to analyze the use of the flipped classroom with the support of the Padlet virtual wall in the geography course, considering data science. There were 28 participants from the O’Farril Irish School, high school, who took the geography course during the 2024 school year. This research was based on the descriptive and causal scope. The sample was non-probabilistic. The results indicate that the use of Padlet before, during and after the classes in the “Spatiality of the economic process and inequality” Unit 4 positively influenced the active role. Likewise, the machine learning algorithm on the decision tree identified 3 models on this virtual wall considering the profile of the students. In the geography course, the students at O’Farril Irish School used Padlet to submit the assignments, share the school activities on the Internet, facilitate the learning, and encourage the autonomy. In conclusion, the flipped classroom and Padlet transformed the role of the students in the geography course through the development of various school activities before, during and after the classes.